2021
DOI: 10.3389/fmicb.2021.631889
|View full text |Cite
|
Sign up to set email alerts
|

DWV Infection in vitro Using Honey Bee Pupal Tissue

Abstract: The deformed wing virus (DWV) has been best characterized among honey bee viruses; however, very little is known regarding the mechanisms of viral infection and replication due to the lack of immortalized honey bee cell lines. To solve this problem, we established an in vitro system using honey bee pupal tissue to reconstruct DWV binding and entry into the host cell, followed by translation of the RNA genome and polyprotein processing using RNA-dependent RNA polymerase (RdRP) as a marker. Using this system, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…We previously showed that rupintrivir suppresses DWV replication in honey bee pupal cells based on the synthesis of RdRP ( 34 ). Thus, we tested the effect of ebselen on DWV replication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that rupintrivir suppresses DWV replication in honey bee pupal cells based on the synthesis of RdRP ( 34 ). Thus, we tested the effect of ebselen on DWV replication.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, ebselen (MW: 274.18) could be a potential lead compound for fragment-based drug discovery approaches to increase the specificity and potency to DWV 3C pro . Rupintrivir and quercetin ( 34 ) as well as ebselen inhibited DWV replication in cultured honey bee cells. Thus, these compounds and the other 3C pro inhibitors we identified in this study could be used to control DWV in honey bee colony.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties are associated with maintaining these cell lines, which may be due to viral infection [ 15 , 17 , 18 ]. In contrast, primary cultured cells have been established from various tissues and organs in the honey bee, and these primary cell cultures are proven to be useful for viral studies and neuronal processes [ 15 , 39 , 40 ]. Although primary cell cultures and ex vivo cultured cells may only be maintained for a limited period of time under healthy conditions, these cells are available for examining gene expression and signaling pathways [ 2 , 5 ].…”
Section: Discussionmentioning
confidence: 99%